Main plots and motives of the cycle about the Eshanoko brothers - Mukhamed F. Bukhurov (Кавказология, 2022)
Songs and legends dedicated to the Eshanoko brothers are one of the most artistically perfect and popular works of oral folk art among the Circassians. Evidence of this is the high frequency of their recording in records and publications, the wide geography of their existence, the diversity and richness of their plot composition. Researchers of the Adyge folklore focused on individual motifs and plots of the cycle under consideration. However, until now there are no special works devoted to a detailed description of the entire plot-motive fund of the cycle about the Eshanoko, which is the reason for our appeal to the designated topic. This study gives, as far as possible, a complete analytical description of the plot and the main motives of the songs and legends included in the named cycle, in connection with which special attention is paid to determining the main plots and motives according to the international indicators (AT, SUS, etc.), established features of the genesis, evolution and transformation of the main plot-forming elements. Because of the study of materials, it is concluded that, as in the Nart epos, folklore universals stand out in the cycle about the Eshanoko brothers, which are the motives and plots about the marriage of the father of the heroes, about their birth, heroic childhood, obtaining a horse, deeds and death. Many of them are like objectification to the elements of a heroic fairy tale. All this allows us to conclude that the cycle about the Eshanoko brothers was formed in close connection with the more ancient genres of the Adyge folklore, in particular, with the archaic Nart epic and heroic tales.